2020 23rd International Symposium on Wireless Personal Multimedia Communications (WPMC) 2020
DOI: 10.1109/wpmc50192.2020.9309496
|View full text |Cite
|
Sign up to set email alerts
|

Overview of 5G New Radio and Carrier Aggregation: 5G and Beyond Networks

Abstract: Recent pandemic has affected the telecom industries with the need for connectivity more than before. It has accelerated the research and innovation activities towards 5G and beyond networks. The purpose of the presented work is to provide the urgency of the situation and state the development with the 5G NR (New Radio). 3GPP launched the standardization activity for 5G system in Release 15, 5G New Radio (NR). This paper presents a comprehensive overview of the development of NR, including deployment scenarios,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…5G is anticipated to augment Network Radios and mm-Wave manipulating a broader spectrum of frequencies from sub-6 GHz to 300 GHz. An outline of Network Radio implementation schemes, involving innovative waveform, frame con gurations and improved radio elements are described in [30]. 5G will overlay centralized cell-less coverage related to users and investigate beyond the use of virtual radio control, non-lineof-sight ecosystems of mm-Wave and optical technology in wireless networks.…”
Section: Paper Structure and Organizationmentioning
confidence: 99%
“…5G is anticipated to augment Network Radios and mm-Wave manipulating a broader spectrum of frequencies from sub-6 GHz to 300 GHz. An outline of Network Radio implementation schemes, involving innovative waveform, frame con gurations and improved radio elements are described in [30]. 5G will overlay centralized cell-less coverage related to users and investigate beyond the use of virtual radio control, non-lineof-sight ecosystems of mm-Wave and optical technology in wireless networks.…”
Section: Paper Structure and Organizationmentioning
confidence: 99%
“…Scheduling is called "Self-Scheduling" when the SG and SA are transmitted on the same cell as the data, and it is known as Cross-Carrier Scheduling (CCS) when SG and SA are transmitted on different cells than the data. For CCS, the Downlink Control Information (DCI) accommodating the SG for a carrier is received on a different carrier [15]. CCS was initially introduced in 3GPP Release 10 [16] with a carrier indicator field (CIF) limited to 3 bits to support aggregation of up to 5 CCs.…”
Section: Cross-carrier Schedulingmentioning
confidence: 99%
“…In addition to the benefits of MC, the limitations and the technical challenges to be faced by using these techniques have also been presented in the literature. In [13] the challenges of using UL and DL CA in 5G are presented. The limitations of different MC schemes in industrial environments have been demonstrated in [14] by conducting measurement campaigns in factories.…”
Section: A Related Workmentioning
confidence: 99%